The World Of Flight - "Gunston, Bill" (Horus Editions Limited: London, 1995)
Explains the principles of flight, and looks at the technology behind both early and modern flying machines and aeroplanes. Suggested level: primary, intermediate, junior secondary
Keywords: Flight